2020
DOI: 10.1101/2020.07.30.227561
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Riluzole suppresses growth and enhances response to endocrine therapy in ER+ breast cancer

Abstract: BackgroundResistance to endocrine therapy in estrogen receptor-positive (ER+) breast cancer remains a significant clinical problem. Riluzole is FDA-approved for the treatment of amyotrophic lateral sclerosis. A benzothiazole-based glutamate release inhibitor with several context-dependent mechanism(s) of action, Riluzole has shown anti-tumor activity in multiple malignancies, including melanoma, glioblastoma, and breast cancer. In several (but not all) of these studies, Riluzole-mediated growth inhibition is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(20 citation statements)
references
References 92 publications
0
20
0
Order By: Relevance
“…Similarly, though ILC are less FDG-avid, the impact of therapy and disease progression on ILC metabolism (and thus FDG avidity) has not been extensively explored outside of anti-estrogen resistant cell line variants. Stires et al reported that while single agent riluzole did not impact growth of ILC PDX HCI-013EI (an estrogen-independent outgrowth of parental HCI-013), combining riluzole with fulvestrant delayed tumor growth longer than fulvestrant alone, supporting that glutamate metabolism is important in ILC tumor response to fulvestrant in vivo [18]. Further, ILC PDX HCI-013 showed intra-tumor metabolic heterogeneity, which was greater in the endocrine resistant HCI-013EI [46].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Similarly, though ILC are less FDG-avid, the impact of therapy and disease progression on ILC metabolism (and thus FDG avidity) has not been extensively explored outside of anti-estrogen resistant cell line variants. Stires et al reported that while single agent riluzole did not impact growth of ILC PDX HCI-013EI (an estrogen-independent outgrowth of parental HCI-013), combining riluzole with fulvestrant delayed tumor growth longer than fulvestrant alone, supporting that glutamate metabolism is important in ILC tumor response to fulvestrant in vivo [18]. Further, ILC PDX HCI-013 showed intra-tumor metabolic heterogeneity, which was greater in the endocrine resistant HCI-013EI [46].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor metabolite tracing, PET-CT studies pairing FDG with other tracers (e.g. 18 F-fluoroestradiol [8,12]), and alternative imaging approaches [47], may facilitate further study of ILC tumor metabolism and metabolic remodeling during therapy response and resistance, and disease progression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations